Mevlevî Hafız Abdülcemîl Efendi’nin Ez-zaferü’l-Hamidiyye Risalesi ve İslâm Kamu Hukukunda hîlafetin kureyşîliği tartışmaları - Hoyladı, Adnan (My University, 2010)
MEVLEVÎ HAFIZ ABDÜLCEMÎL EFENDĠ’NĠN EZ-ZAFERU’L-HAMÎDĠYYE RĠSALESĠ VE ĠSLÂM KAMU HUKUKUNDA HĠLÂFETĠN KUREYġÎLĠĞĠ TARTIġMALARI Kureyşilik tartışmaları ilk olarak Hz. Ebûbekir’in halife seçiminde yapılmıştır. Hz. Ebûbekir Sakîfe toplantısında halifenin Kureyş kabilesinden seçilmesi gerektiğini ifade etmiştir. Hilafetin Osmanlılara geçişiyle tekrar gündeme gelen Kureyşilik tartışmaları özellikle Osmanlının son dönemlerinde siyasi sebeplerden dolayı iyice alevlenmiştir. Osmanlı halifesinin Hindistan’da Müslümanların lideri rolünü üstlenmesini istemeyen İngilizler, bu bölgede halifenin Kureyş’ten olması gerektiği propagandası yaptılar. Aynı propagandayı Araplara karşı da yapan İngilizler, onların Osmanlıdan ayrılmalarını amaçladılar. Meselenin hukuki boyutunu ise Hz. Peygamber’in Kureyş lehine olan ifadeleri şekillendirmektedir. Bir kısım ulema bu konudaki hadislere dayanarak halifenin Kureyşten olması gerektiğini söylerken bir kısım ulema da bu hadisleri çeşitli tevillere tabi tutarak bu şarta karşı çıkmıştır. Mevlevî Hafız Abdülcemîl Efendi de Kureyşilik şartına yazdığı risalesinde karşı çıkmış, bu şekilde İngilizlerin propagandalarına karşı bölge Müslümanlarını bilgilendirmiştir.

MAWLAVĠ HAFIZ ABDUL JAMIL EFENDI’S TREATISE CALLED AS EZZAFERU’L- HAMIDIYYE AND DISCUSSION ABOUT THE CALIPHATE'S BEING QURAISHI IN ISLAMIC CIVIL LAW First discussions about that caliph must be one of Quraysh tribe, was took place in the caliphate election of Hz. Ebûbekir. Hz. Ebûbekir stated that the caliphate must be elected from the Quraysh tribe in the Sakîfe meeting. Debate of Qurayshi which came into the agenda again with the transition of Caliphate to the Otomans, was thoroughly overwhelmed especially at the end of the Ottoman period because of the political reasons. Britishs who did not want to the Otoman caliphate to get the leadership role of the Muslims in India, did propaganda about the caliphate must be descending from Quraysh tribe, in this region. Britishs also did the same propaganda against Arabs , intended to leave Muslim of this region from the Ottomans. Expressions of Prophet for Quraysh shape the legal issues of the matter. Some scholars say that caliphate sould be Quraysh based on hadith about this subject and same of this oppose Qurayshi condition by various gloss of hadith. Abdul Jamil opposed condition of Qurayshi in his treatise thereby he informed Muslims against British propaganda.
Keywords: Hilafet; İslam Hukuku